2018
DOI: 10.1038/s41598-018-20388-z
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Analogues of the parasitic worm product ES-62 interact with the TIR domain of MyD88 to inhibit pro-inflammatory signalling

Abstract: ES-62 is a protein secreted by the parasitic worm Acanthocheilonema viteae that is anti-inflammatory by virtue of covalently attached phosphorylcholine. Previously we have reported that drug-like Small Molecule Analogues (SMAs) of its phosphorylcholine moiety can mimic ES-62 in protecting against disease development in certain mouse models of autoimmune and allergic conditions, due to them causing partial degradation of the TLR/IL-1R adaptor MyD88. We have now taken a molecular modelling approach to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…Fig. S3G shows that co-immunoprecipitation (co-IP) samples from cells treated with IL-1β produced stronger bands than from cells not untreated samples, as shown by others 64 . Cells were lysed in Ripa buffer in the presence of protease inhibitors and incubated on ice for 25 min.…”
Section: Methodssupporting
confidence: 74%
“…Fig. S3G shows that co-immunoprecipitation (co-IP) samples from cells treated with IL-1β produced stronger bands than from cells not untreated samples, as shown by others 64 . Cells were lysed in Ripa buffer in the presence of protease inhibitors and incubated on ice for 25 min.…”
Section: Methodssupporting
confidence: 74%
“…Our examinations to date indicate that active SMAs like 11a and 12b mimic a primary ES-62 mechanism of action in causing autophagolysosomal degradation of the TLR/IL-1R adaptor molecule MyD88 (Al-Riyami et al, 2013;Rzepecka et al, 2015b;Rodgers et al 2015). Indeed, recently we have found that this reflects direct interaction between the SMAs and the TIR domain of MyD88 (Suckling et al 2018).…”
Section: Introductionmentioning
confidence: 70%
“…Finally, it has recently become apparent that the primary effect of ES-62 and the SMAs on immune system cells is to down-regulate the aberrantly elevated MyD88-dependent responses pertaining during chronic inflammation, restoring them back towards the steady-state levels observed in healthy animals. This has been observed with macrophages [ 6 ], dendritic cells [ 51 ], mast cells [ 52 ], and Th17 cells [ 30 ], and at least in the case of the SMAs, has been shown to reflect direct interaction with the MyD88 TIR domain [ 53 ]. Interestingly, mice lacking MyD88 are resistant to the development of EAE [ 54 ] and this may suggest that ES-62/SMAs’ mechanism of action involving reduction rather than the abrogation of adaptor levels [ 6 , 30 , 51 , 52 ] may be insufficient to achieve protection against inflammatory responses in this particular model.…”
Section: Discussionmentioning
confidence: 97%